(untitled) (International Journal of Environmental Sciences, 2025)
Himachal Pradesh is very susceptible for the Landslide induced disasters due to its geographical and seismic characteristics. Its high seismic activities, fragile mountains and anthropogenic activities are significant contributor of occurrence of landslides. In recent years, the state has experienced numerous catastrophic events that has resulted in loss of lives, environment degradation, and substantial geographical alterations. In many incidents, due to its rugged terrain, inadequate infrastructure and adverse circumstances have often stalled government/ other agencies rescue efforts. Many villages in the state lack road connectivity, leaving residents isolated and reliant on self-help during landslide induced disasters. In these circumstances, Local community volunteer to conduct the necessary action before any aid is received. Essential machineries or equipment are also of not any use as they cannot be transported to these far-flung areas due to either no connectivity or poor quality of roads, or road blockage due to landslips. The absence of adequate quality infrastructure often results in failure of response mechanism, no matter how effective it is resulting in losses to lives and damages to infrastructure. In this scenario, the capacity building and empowerment of community in preparedness and mitigation is paramount to make them disaster resilient. Local community has invaluable geographical and traditional knowledge enabling them to immediate response to the incident and rescue the people and live-stokes. Conducting regular training and mock drills, installing landslide early warning systems, use of modern technologies and artificial intelligence in all three phases of disaster, constructing tunnels bypassing highly vulnerable areas, constructing Heli-pads and restrict use of heavy machineries will facilitate community in managing landslide induced disasters. Community-Based Disaster Management (CBDM) is a proactive and inclusive approach that engages local populations in preparedness, response, and mitigation domains.